The Rotator Interval Bursa (RIB) Technique: Sequential Rotator Interval and Subacromial Subdeltoid Bursa Injection - Nischal, Neha; Mishra, Chetna; Singh, Jatinder Pal (Indian Journal of Radiology and Imaging, 2024)
Shoulder pain is a common and increasing indication for patients being referred for pain relief injections. To address this, patients are offered corticosteroid injections for the glenohumeral joint as well as the subacromial subdeltoid (SASD) bursa under ultrasound guidance, which allows direct visualization of the needle and target structures with a more confident and real-time needle placement. We demonstrate a new technique, the rotator interval bursa (RIB) technique, of sequential injection of the glenohumeral joint targeting the rotator interval as well as the SASD bursa via the anterior approach with a single prick.
Keywords: ultrasound; shoulder pain; anterior approach; RIB technique; corticosteroid injection; rotator interval; subacromial-subdeltoid bursa